The main types of wind turbines-generators in the power supply system - S. K. Sheryazov; S. S. Issenov; R. M. Iskakov; A. B. Kaidar (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. Conduct a detailed analysis of existing wind turbines. Analyze the role, place and features of the functioning of wind power plants. Provide various options for generators and schemes for converting wind energy into electricity. Provide recommendations for improving the reliability of wind turbines in smart grids.METHODS. The article was prepared using analytical methods, statistical, theoretical, factorial and technical methods.RESULTS. A fixed speed asynchronous generator used in a wind power conversion system (WECS) without a power converter interface draws a significant portion of the reactive power from the grid. This configuration features simple, reliable operation. Wind turbine asynchronous generator with dual power supply. can improve overall power conversion efficiency by performing maximum power point tracking (MPPT), and an increase in speed of about 30% can improve dynamic performance and increase resilience to system disturbances that are not available for turbine types 1 and 2. The use of full-scale 100% power converters will significantly increase the productivity of SPEV wind energy conversion systems, but will slightly increase the cost of the power converter, up to 7% - 12% of the total equipment cost. By using a large number of pole pairs for all types of permanent magnet synchronous generator (PMG), the turbine gearbox can be removed. This type of wind energy conversion system is more resilient to grid disruptions compared to type 1, 2 and 3 wind systems. The review shows that types 3 and 4 technologies are used to most efficiently sell and recycle wind turbines in electricity markets.CONCLUSION. The article analyzes the features of the functioning of wind power plants operating on the grid. Various options for generators and schemes for converting wind energy into electricity are presented. A detailed analysis of existing wind turbines is provided. Recommendations are given for improving the reliability and efficiency of wind power plants in smart grids.